Structural response reconstruction with transmissibility concept in frequency domain - Law, S.; Li, Jun; Ding, Y. (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2011)
This paper presents a method for structural response reconstruction in the full structure or in a substructure, using the generalized transmissibility concept in frequency domain. The response reconstruction is based on transforming the measured responses into responses at other selected locations with the transmissibility matrix. The use of transmissibility concept in a substructure for response reconstruction is introduced by taking the interface forces at the interface degrees-of-freedom as input excitations. The First-Order-Hold input approximation is used in the forward response calculation to improve the accuracy of the dynamic response analysis. Numerical studies on a seven-storey plane frame structure are conducted to investigate the accuracy and efficiency of the proposed method and the effects of influencing parameters, such as the system sampling duration, sampling rate, sensor numbers and measurement noise are studied. Accurate reconstruction is achieved in all studies when there is significant vibration in the measured responses.